NEW PROVIDERS IN THE HIGHER EDUCATION MARKET - Margarita V. Pashkovskaya (Высшее образование в России)
Globalization, commercialization and virtualization of higher education led to the transformation of traditional functions of universities and the emergence of new types of training providers. Traditional universities, on the one hand, keeping the historical features, objectives and functions actively use modern educational tools provided by scientific and technological revolution, on the other hand, some traditional universities are activelymodifying and integrating into a modern educational infrastructure. The role of new providersof higher education, both national and international, is constantly growing. There are new kinds of educational providers, more compliant the higher education market and opportunities of modern educational technologies. New providers can be conditionally divided into two large groups - the actual educational institutions and non-education providers to ensure these educational processes. Activities of new providers significantly changes the landscape ofhigher education market - an increasing number of market participants of educational services,that specialize in certain functions of the educational process, the merging of higher education providers and manufacturing companies.